2021
DOI: 10.1016/j.ccell.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of tumor cell states and ecosystems in diffuse large B cell lymphoma

Abstract: Highlights d Large-scale profiling of cell states & cellular ecosystems in hematologic malignancies d Atlas of malignant B cell states and 12 cell types in the DLBCL tumor microenvironment d Nine DLBCL cellular ecosystems & their relationships to molecular subtypes and survival d Candidate cellular biomarkers of response to bortezomib in DLBCL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 96 publications
1
102
0
Order By: Relevance
“…Next, we investigated the role of PD-1 and A2aR in the phenotype of dysfunctional CD8 + T cells at the single-cell RNA expression level using the publicly available dataset GSE182434. 20 CD8 + T cells had been annotated in four DLBCL samples. We further classified CD8 + T cells into seven clusters by Seurat ( figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the role of PD-1 and A2aR in the phenotype of dysfunctional CD8 + T cells at the single-cell RNA expression level using the publicly available dataset GSE182434. 20 CD8 + T cells had been annotated in four DLBCL samples. We further classified CD8 + T cells into seven clusters by Seurat ( figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…The processed dataset (GSE182434) of publicly available data for single-cell RNA sequencing was downloaded from the NCBI GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ). 20 CD8 + T cells had been annotated in four DLBCL samples. We then used Seurat v3.1.2 21 to normalize and scale the expression matrices by function NormalizeData and ScaleData.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a study using microarray-based GEP in 23 PCNSL cases demonstrated overlapping expression of germinal-center and activated B-cell genes [37]. In line with these findings, recent studies in DLBCL-NOS also demonstrated that binary classification into ABC or GCB does not correspond to the more complex biology as identified by transcriptomics and that recurrent genetic alterations are identified beyond the established COO subtypes [38][39][40].…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the poor correspondence and high percentage (43%) of UI may suggest a different biology of PCDLBCL-LT compared with DLBCL-NOS for which these algorithms were originally developed. Future studies need to investigate this observation with more comprehensive transcriptomic analysis, such as the EcoTyper, as recently described by Steen et al [40].…”
Section: Discussionmentioning
confidence: 96%
“…IN-LME is enriched in CD8 + T cells and a subpopulation of CD8 + T cells with high PD-1 expression and high expression of the immune checkpoint molecule PD-L1 and the tryptophanolytic enzyme IDO1, suggesting that this LME class may benefit from ICIs treatment. Steen CB et al characterized clinically relevant DLBCL cell states and ecosystems with EcoTyper (a machine-learning framework integrating transcriptome deconvolution and single-cell RNA sequencing), identified 5 cell states of malignant B cells with different prognostic associations and differentiation status, and revealed nine multicellular ecosystems in DLBCL, known as lymphoma ecotypes (LE) ( Steen et al, 2021 ). They found T-cell transcriptomic heterogeneity in DLBCL and that tumors high in LE4 are characterized by an immunoreactive T-cell state with widespread expression of co-inhibitory and stimulatory molecules, with potential implications for immunotherapeutic targeting.…”
Section: Discussionmentioning
confidence: 99%